A Living Conversation - Sponheim, Paul R. (Dialog, 2003)
Experiencing strong differences regarding Christian faith in his family of origin, Paul Sponheim came to stress the content of Christian faith as something to be explicated and defended. The framework for that work has been the distinction and relationship between self and world in relation to God. S. Kierkegaard and A.N. Whitehead are seen as major influences (self, world; respectively) and as needing each other in faith's appropriation. Five decades of theological work constitute a conversation, including teaching and writing. In closing the question of the efficacy of such a conversation is raised and appeal is made to the transformative power of genuine conversation in which all participants are fully present.